The structure of the C-terminal domain of the nucleoprotein from the Bundibugyo strain of the Ebola virus in complex with a pan-specific synthetic Fab - Radwańska, Malwina J. (Acta Crystallogr D Struct Biol, 2018)
The vast majority of platforms for the detection of viral or bacterial antigens rely on immunoassays, typically ELISA or sandwich ELISA, that are contingent on the availability of suitable monoclonal antibodies (mAbs). This is a major bottleneck, since the generation and production of mAbs is time-consuming and expensive. Synthetic antibody fragments (sFabs) generated by phage-display selection offer an alternative with many advantages over Fabs obtained from natural antibodies using hybridoma technology. Unlike mAbs, sFabs are generated using phage display, allowing selection for binding to specific strains or for pan-specificity, for identification of structural epitopes or unique protein conformations and even for complexes. Further, they can easily be produced in Escherichia coli in large quantities and engineered for purposes of detection technologies and other applications. Here, the use of phage-display selection to generate a pan-specific Fab (MJ20), based on a Herceptin Fab scaffold, with the ability to bind selectively and with high affinity to the C-terminal domains of the nucleoproteins (NPs) from all five known strains of the Ebola virus is reported. The high-resolution crystal structure of the complex of MJ20 with the antigen from the Bundibugyo strain of the Ebola virus reveals the basis for pan-specificity and illustrates how the phage-display technology can be used to manufacture suitable Fabs for use in diagnostic or therapeutic applications.